The Transformation of Monopoly Game: Learning Media to Improve Students' Creativity and Interest in Learning - Hastanti, Atika Dinna (Proceeding International Conference on Science and Engineering, 2020)
This study aims to determine and applying how effective the design of The Transformation of Monopoly Game as a learning media in order to increase students' creativity and interest in learning. Technological progress has been rapid development in various fields such as social, political, cultural, economic and even education. Due to technological advances often cause trends and addictions to technology, especially among students. Based on a Study funded by UNICEF (United Nations Children’s Fund) and carried out by the Ministry of Communication and Information by tracking online activities of a sample of children and adolescents aged 10-19 (as many as 400 respondents). The results of this study state the use of social media and digital become an integrated part in the daily lives of Indonesian young people. The study found that 98% of the children and adolescents surveyed knew about the internet and that 79.5% of them were internet users. This research uses descriptive method and action research. Descriptive method is used to describe the phenomena that are taking place now or in the past, and collect data from journals, book, as well as other sources. Then by applying the action research method which research objects use in the learning process. Through this media students not only play but also learn, so this can find out how effective The Transformation of Monopoly Game is as a learning medium in order to increase students' creativity and interest in learning.